Corporate governance and anti-money laundering measures in the banking industry: Malaysian experience - A. Rahman, Aspalella (International Academic Research Journal, 2015)
Money laundering has been described by many as the lifeblood of crime and is a major threat to the economic and social well-being of societies. Malaysia passed the Anti-Money Laundering and Anti-Terrorism Financing Act (AMLATFA) in 2001. AMLATFA not only criminalizes money laundering, but also emphasizes on good corporate governance and senior management accountability.Banks as the main reporting entities have borne the brunt of the measures introduced by the law.This paper will highlight the importance of corporate governance in anti-money laundering measures.As such, the discussion will focus on the roles and responsibilities of the board of directors and senior management to put in place relevant antimoney laundering (AML) measures as prescribed by AMLATFA.Undoubtedly, effective AML measures significantly impact on the efficiency of a bank’s corporate governance which is considered a key element in ensuring that the bank is operated in a safe and sound manner.More importantly, an efficient AML measure with good governance lower the pervasiveness of money laundering activities. At the end of the day this is the duty that the bank’s board of directors owe to their stakeholders.